2008
DOI: 10.1021/nl802353x
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Internal Quantum Efficiency of PbSe Nanocrystal Solar Cells with the Aid of an Optical Model

Abstract: We determine the internal quantum efficiency (IQE) of the active layer of PbSe nanocrystal (NC) back-contact Schottky solar cells by combining external quantum efficiency (EQE) and total reflectance measurements with an optical model of the device stack. The model is parametrized with the complex index of refraction of each layer in the stack as calculated from ellipsometry data. Good agreement between the experimental and modeled reflectance spectra permits a quantitative estimate of the fraction of incident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
164
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 168 publications
(174 citation statements)
references
References 19 publications
9
164
1
Order By: Relevance
“…A detailed optical and electrical model of the device parametrized by ellipsometry measurements has been developed to help answer this question. 21 However, we have also recently found that the EDT treatment of our PbSe NC films, while enhancing their PV performance, suppresses MEG. 22 Quenching of the MEG quantum yield by the EDT treatment potentially explains why the estimated IQE values reported here do not exceed 100%.…”
mentioning
confidence: 71%
“…A detailed optical and electrical model of the device parametrized by ellipsometry measurements has been developed to help answer this question. 21 However, we have also recently found that the EDT treatment of our PbSe NC films, while enhancing their PV performance, suppresses MEG. 22 Quenching of the MEG quantum yield by the EDT treatment potentially explains why the estimated IQE values reported here do not exceed 100%.…”
mentioning
confidence: 71%
“…101 The photogeneration profile (green line, bottom graph) decays exponentially with the extinction length of 400 nm, typically for 1 μm wavelength light in a PbSe nanocrystal film. 5 The actual current collected under short-circuit (green fill, bottom graph), is the multiplication of the generation profile and collection probability, and drops significantly outside of the space charge region. where ε is the dielectric constant, ε 0 is the permittivity of free space, and q is the fundamental charge.…”
Section: −63mentioning
confidence: 99%
“…2 Accordingly, colloidal PbSe QDs can be engineered to absorb and emit in a vast spectral range, spanning from ∼800 to 4000 nm with high photoluminescence (PL) emission quantum yields (QYs). [3][4][5][6][7][8] Hence, PbSe QDs are important materials for near-IR (NIR; >700 nm) and mid-IR (>2500 nm) applications, including biological imaging/labeling, 9,10 solar cells, [11][12][13][14][15][16] light-emitting devices, 17 and telecommunications. 18,19 PbSe nanocrystals (NCs) are especially attractive in the PV application, with a multiple exciton generation effect reported.…”
Section: ' Introductionmentioning
confidence: 99%